Closeness-inducing discussions with a romantic partner increase cortisol and testosterone. (October 2021) - Chin, Kristi; Reese, Zachary A.; Ascigil, Esra; Sim, Lester; Edelstein, Robin S.
Abstract: Despite progress in understanding the social neuroendocrinology of close relationship processes, most work has focused on negative experiences, such as relationship conflict or stress. As a result, much less is known about the neuroendocrine implications of positive, emotionally intimate relationship experiences. In the current study, we randomly assigned 105 dating or married couples to a 30-minute semi-structured discussion task that was designed to elicit either high or low levels of closeness. Participants provided pre- and post-task saliva samples (to assess cortisol and testosterone) and post-task reports of self-disclosure, closeness, attraction, positive and negative affect, and stress. Participants found the discussion conditions comparably positive and enjoyable, but those in the high-closeness condition reported that they disclosed marginally more and felt marginally closer to their partners than those in the low-closeness condition. Participants also showed larger increases in cortisol and testosterone during the high (versus low) closeness discussion, and self-reported disclosure mediated these increases in cortisol and testosterone. Self-reported closeness and other theoretically plausible mediators, such as sexual attraction and excitement, did not mediate changes in either hormone. Taken together, the current findings contribute to our understanding of neuroendocrine changes associated with emotionally intimate relationship experiences. We consider possible explanations for the hormone changes we observed and offer directions for future research on the neuroendocrine implications of close relationship experiences. Highlights: Assessed cortisol and testosterone changes during romantic partner discussions. People showed hormones increases in high (vs. low) closeness discussion condition. Self-reported disclosure during the discussion mediated hormone increases.